A comparison of the effects of beaver ponds and forest harvest on stream methylmercury in boreal watersheds - W Y Lam; R W Mackereth; C M E Lajoie; K A Kidd; C P J Mitchell (Environmental Research: Ecology)
Beaver ponds and forest harvest are common disturbances in the Canadian boreal forest that result in major changes to catchment hydrology and thus also influence the mobilization and methylation of mercury (Hg). Though both beaver ponds and forest harvest frequently occur in the same watersheds, the possible interactive effects are not well understood. To evaluate the comparative effects of these two disturbances, this study examined in-stream total mercury and methylmercury (MeHg) across 7 stream reaches in the central Canadian boreal forest. Results showed that downstream-to-upstream MeHg concentration ratios were more highly correlated to the presence of beaver ponds than to the presence of forest harvest. However, MeHg concentrations upstream of ponds were higher in streams within harvested watersheds; these streams demonstrated a weaker correlation between beaver pond presence and downstream-to-upstream MeHg concentration ratios. Understanding these comparative and cumulative effects of beaver ponds and forest harvest will allow forest managers to consider how harvest activity could affect downstream MeHg in areas with high beaver activity.